CFD modeling the diffusional losses of nanocluster-sized particles and condensing vapors in 90° bends of circular tubes. (December 2020) - Olin, Miska; Dal Maso, Miikka
Abstract: Particle and vapor measurements typically include sampling tubing causing sampling losses therein. Correcting measured concentrations from the sampling losses using the calculated penetration efficiencies of straight tubes is a satisfactory approximation if sub-micrometer particles are of interest. However, in addition to inertial impaction of larger particles, bends in the tubing can cause a significant increase in diffusional losses of particles smaller than 5 nm or of condensing vapor, such as sulfuric acid. Here, the effects of 90° bends with various curvatures (dimensionless curvatures of 1.3 − 67 ) on the diffusional losses in a wide range of Reynolds ( 25 − 10000 ) and Schmidt ( 0.48 − 1400 ) numbers were simulated using computational fluid dynamics. The results were parametrized to output the functions for the penetration efficiencies of a bend. Highlights: Diffusional losses of particles and vapors in tubes exhibit effects from bent parts. The effects of bends are considerable for particles smaller than 5 nm. A bend can decrease the penetration of sulfuric acid by tens of percents. Parametrizations for the effects of 90-degree bends are constructed.